2017
DOI: 10.3390/genes8050142
|View full text |Cite
|
Sign up to set email alerts
|

MYC—Master Regulator of the Cancer Epigenome and Transcriptome

Abstract: Overexpression of MYC is a hallmark of many human cancers. The MYC oncogene has long been thought to execute its neoplastic functions by acting as a classic transcription factor, deregulating the expression of a large number of specific target genes. However, MYC’s influence on many of these target genes is rather modest and there is little overlap between MYC regulated genes in different cell types, leaving many mechanistic questions unanswered. Recent advances in the field challenge the dogma further, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 192 publications
(268 reference statements)
1
116
0
2
Order By: Relevance
“…Koga et al, () demonstrated that miR‐302 induces H3K4 methylation through downregulation of AOF2, resulting in MYC repression, apoptosis, and drug sensitivity in hepatocellular carcinoma cells. Considering the oncogenic function of MYC and its pivotal role as a master regulator of the cancer epigenome and transcriptome (Poole & van Riggelen, ), downregulation of MYC by miR‐302 cluster may explain some of the anti‐tumor effects of miR‐302 cluster we observed in breast cancer cells. Sustaining proliferative signaling is one of the fundamental features of cancer development (Hanahan & Weinberg, ).…”
Section: Discussionmentioning
confidence: 90%
“…Koga et al, () demonstrated that miR‐302 induces H3K4 methylation through downregulation of AOF2, resulting in MYC repression, apoptosis, and drug sensitivity in hepatocellular carcinoma cells. Considering the oncogenic function of MYC and its pivotal role as a master regulator of the cancer epigenome and transcriptome (Poole & van Riggelen, ), downregulation of MYC by miR‐302 cluster may explain some of the anti‐tumor effects of miR‐302 cluster we observed in breast cancer cells. Sustaining proliferative signaling is one of the fundamental features of cancer development (Hanahan & Weinberg, ).…”
Section: Discussionmentioning
confidence: 90%
“…[17,27,28] The sheer number and variety of MYC targets has sparked intense interest in both regulatory mechanisms and function. Detailed analysis of MYC function have been reviewed comprehensively elsewhere, [29][30][31] and although a complete discussion is beyond the scope of this review, we provide some brief background. MYC is a member of the basic helix-loop-helix (bHLH) protein family, which heterodimerizes with its binding partner MAX to stimulate transcription.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogenic protein c-Myc, which is constitutively expressed in a variety of aggressive tumors, including glioblastomas, acts not only as a transcription factor, but as a global regulator of pro-tumor epigenetic modifications (57). We found that c-Myc expression in U87 cells underwent a rapid decline after PDT, beginning immediately after irradiation, reaching a nadir at ~3 h, and then gradually rising so that the c-Myc level at 24 h approximated that of the nonirradiated control (Fig.…”
Section: Jq1-inhibitable Induction Of Other Prosurvival/pro-invasion mentioning
confidence: 99%